1995
DOI: 10.1002/j.1537-2197.1995.tb12680.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal dynamics of three woodland herbs of contrasting phenology along topographic gradients

Abstract: Vesicular‐arbuscular mycorrhizal (VAM) dynamics of three woodland herbs of differing phenology were examined along contiguous topographic gradients in two southwestern Ohio forests during 1992‐1994. Cardamine concatenata (Brassicaceae) exhibited VAM colonization only during senescence in May, whereas Trillium flexipes and Smilacina racemosa exhibited robust VAM development throughout the year. The lowest mean percent root length colonized (PRLC) for T. flexipes and S. racemosa was 38.3% and 37.7%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Buxbaum show only traces of root colonization by AM fungi (Carrillo-García et al 1999). Our finding of a lower percentage of root length colonized by arbuscules at ZTJ and SRZ than at AJ corroborate these studies and provide further evidence that the capacity for symbiosis with AM fungi is associated with favorable conditions for photosynthesis by the host plant (DeMars andBoerner 1995, Smith andSmith 1996).…”
Section: Study Sitesupporting
confidence: 83%
“…Buxbaum show only traces of root colonization by AM fungi (Carrillo-García et al 1999). Our finding of a lower percentage of root length colonized by arbuscules at ZTJ and SRZ than at AJ corroborate these studies and provide further evidence that the capacity for symbiosis with AM fungi is associated with favorable conditions for photosynthesis by the host plant (DeMars andBoerner 1995, Smith andSmith 1996).…”
Section: Study Sitesupporting
confidence: 83%
“…The higher resorption of P in bottomland sites may, in part, be reflected by the means in which Lonicera maackii obtains P. The Caprifoliaceae form vesicular-arbuscular mycorrhizae, which increase the absorption of soil P (Trappe, 1987). DeMars and Boerner (1995) showed that there were significantly lower levels of mycorrhizal colonization in herbaceous understory plants in the moister bottomlands of the study sites. Hence, the combination of low soil P availability and lower mycorrhizal development may necessitate greater P conservation.…”
Section: Discussionmentioning
confidence: 82%
“…Standard errors of the mean are given in parentheses. Data are adapted from DeMars and Runkle (1992), DeMars and Boerner (1995 (Chapman, 1965).…”
Section: Methodsmentioning
confidence: 99%
“…Rice bran oil is used for making soap and cosmetics (8). Certain studies revealed that AM fungi root colonization has seasonal dynamics (9,10). Rice plants readily form mycorrhizal associations under upland conditions and limited colonization occurs under submerged conditions due to the anoxic environment (11).…”
Section: Introductionmentioning
confidence: 99%